(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2018)
The process of creating and maintaining citizen serving public space is interest to a wide range of city design professionals and public officials.Â The Project for Public Space has found that successful projects possess four qualities: they are accessible; people are engaged in activities there; the space is comfortable; and it is a sociable place: one where people meet each other and take people when they come to visitÂ (www.pps.org). Using these qualities as a framework this article explores the Japanese practice of placing small Buddhist shrines in neighborhoods, and examining how the shrines function as public spaces.